Young nights - of choices and relatable experiences - Syahir Ezekiel Rafa'ee (Jack) (2018)
In this paper written by the Director of the short film, "Young Nights", Syahir journals his research processes, ideas and inspirations that aided him towards producing a short film for his Final Year Project.